Kiko Denzer: Build your own Earth Oven - Davidson, Alan (Petits Propos Culinaires, 2024)
Kiko Denzer: Build your own Earth Oven: Handprint Press, Blodgett OR, 2000: ISBN 0-9679846-0-2: 127 pp., plenty of b&w and colour illus., p/b, 14.95.